Age- and Wavelength-Dependency of Drosophila Larval Phototaxis and Behavioral Responses to Natural Lighting Conditions - Humberg, Tim-Henning; Sprecher, Simon G. (Frontiers in Behavioral Neuroscience, 2017)
Animals use various environmental cues as key determinant for their behavioral decisions. Visual systems are hereby responsible to translate light-dependent stimuli into neuronal encoded information. Even though the larval eyes of the fruit fly Drosophila melanogaster are comparably simple they comprise two types of photoreceptor neurons, defined by different Rhodopsin genes expressed. Recent findings support that for light avoidance Rhodopsin5 expressing photoreceptors are crucial, while Rhodopsin6 expressing photoreceptors are dispensable under laboratory conditions. However, it remains debated how animals change light preference during larval live. We show that larval negative phototaxis is age-independent as it persists in larvae from foraging to wandering developmental stages. Moreover, if spectrally different Rhodopsins are employed for the detection of different wavelength of light remains unexplored. We found that negative phototaxis can be elicit by light with wavelengths ranging from ultraviolet to green. This behavior is uniquely mediated by Rhodopsin5 expressing photoreceptors, and therefore suggest that this photoreceptor-type is able to perceive ultraviolet up to green light. In contrast to laboratory our field experiments revealed that Drosophila larvae uses both types of photoreceptors under natural lighting conditions. All our results, demonstrate that Drosophila larval eyes mediate avoidance of light stimuli with a wide, ecological relevant range of quantity (intensities) and quality (wavelengths). Thus, the two photoreceptor-types appear more likely to play a role in different aspects of phototaxis under natural lighting conditions, rather than color discrimination.